THE QUALITY OF ENGLISH TRANSLATION VERSION OF BILINGUAL BOOKS FOR PHYSICS AND SOCIAL SCIENCE - Djatmika .; Agus Hari Wibowo; Ida Kusuma Dewi (Humaniora, 2014)
This article discusses the quality of English translation of the course books of Physics, Economics, and History for Junior High School students in Indonesia. The research which becomes the base for the article is qualitative, conducted on five English version texts of bilingual books for Junior High School students in Indonesia. It selected one chapter of each book and analyzed the quality of its text structure as well as its text texture. The data were in the forms of discourse units and analyzed on the quality of the text structure and aspects of grammar quality such as the grammatical construction of the clauses and the lexical choices of the texts. In addition, it obtained data related to the readability of the texts from twenty students who were selected randomly. The results show that all of the English texts have good quality in their text structure. However, the grammar and choice of words show a number of weaknesses in each text. Text improvement should consider English grammatical rules and systems and Indonesian language interference for English grammatical constructions, word choice and technical terms.